Non-cirrhotic portal hypertension secondary to cholangiointestinal anastomotic stricture after choledochal cyst excision: a case report - Zhang, Xu; Yan, Jun Qing; Gao, Yan Ying; Song, De Zhao; Lou, Cheng (Frontiers in Medicine, 2023)
Background Cystectomy accompanied by biliary system reconstruction is an important treatment option for choledochal cysts, but the risk of post-operative complications is high. The most famous long-term complication is anastomotic stricture, whereas non-cirrhotic portal hypertension secondary to cholangiointestinal anastomotic stricture is rare. Case summary Here we report the case of a 33-year-old female patient with a type I choledochal cyst who underwent choledochal cyst excision with Roux-en-Y hepaticojejunostomy. Thirteen years later, the patient presented with severe esophageal and gastric variceal bleeding, splenomegaly, and hypersplenism. Furthermore, cholangiointestinal anastomotic stricture with cholangiectasis was identified on imaging. A pathological examination of the liver suggested intrahepatic cholestasis, but the fibrosis was mild and inconsistent with severe portal hypertension. Therefore, the final diagnosis was portal hypertension secondary to a cholangiointestinal anastomotic stricture after choledochal cyst surgery. Fortunately, the patient recovered well after endoscopic treatment and dilated cholangiointestinal anastomotic stricture. Conclusion Choledochal cyst excision with Roux-en-Y hepaticojejunostomy is the recommended standard of care for type I choledochal cysts; however, the long-term risk of cholangiointestinal anastomotic stricture requires consideration. Moreover, cholangiointestinal anastomotic stricture can lead to portal hypertension, and the degree of elevated portal pressure may be inconsistent with the degree of intrahepatic fibrosis.